2013
DOI: 10.1186/2193-1801-2-402
|View full text |Cite
|
Sign up to set email alerts
|

β-galactosidase stability at high substrate concentrations

Abstract: Enzymatic synthesis of galacto-oligosaccharides is usually performed at high initial substrate concentrations since higher yields are obtained. We report here on the stability of β-galactosidase from Bacillus circulans at 25, 40, and 60°C in buffer, and in systems with initially 5.0 and 30% (w/w) lactose. In buffer, the half-life time was 220 h and 13 h at 25 and 40°C, respectively, whereas the enzyme was completely inactivated after two hours at 60°C. In systems with 5.0 and 30% (w/w) lactose, a mechanistic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 21 publications
(32 reference statements)
3
24
0
Order By: Relevance
“…Palai et al () observed an increase in the formation of total GOS (i.e., the sum of DP3–5 fractions) from 22 to 39% as the initial lactose concentration increased from 55 to 525 g L −1 . Also, results of Warmerdam, Boom, et al () determined at 5 w/w% and 30 w/w% lactose concentration agree well with our observations under similar conditions but using different source of substrate. However, our results lay clearly below the high yields reported by Sen et al () for Biolacta FN5 using UF whey permeates in STR.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Palai et al () observed an increase in the formation of total GOS (i.e., the sum of DP3–5 fractions) from 22 to 39% as the initial lactose concentration increased from 55 to 525 g L −1 . Also, results of Warmerdam, Boom, et al () determined at 5 w/w% and 30 w/w% lactose concentration agree well with our observations under similar conditions but using different source of substrate. However, our results lay clearly below the high yields reported by Sen et al () for Biolacta FN5 using UF whey permeates in STR.…”
Section: Resultssupporting
confidence: 92%
“…Our results on GOS yields compare well with the yields reported for STR using buffered solutions of (pure) lactose (Palai et al, ; Warmerdam, Boom, & Janssen, ). Palai et al () observed an increase in the formation of total GOS (i.e., the sum of DP3–5 fractions) from 22 to 39% as the initial lactose concentration increased from 55 to 525 g L −1 .…”
Section: Resultssupporting
confidence: 90%
“…Continuing fermentation, the glucose concentration decreased due to the formation of novel oligosaccharides (Cezar et al, 2018). As shown by several researchers (Bojan et al, 2011;Goderska et al, 2008;Warmerdam et al, 2013), lactose hydrolysis with Bifidobacterium bifidum β-galactosidase showed high activity significantly reducing initial lactose amount in substrates. It influences the final monosaccharides concentration, especially higher glucose yield.…”
Section: Figure 1 the Effect Of Fermentation Process On The Monosaccmentioning
confidence: 78%
“…The enzyme showed increased stability in the presence of its substrate. Significant stability of inulinase for hydrolyzing inulin up to ten cycles at 60°C may be attributed to the conformational change or conformational tightening of enzyme in the presence of its substrate [13,26,28]. Decrease in the sugar yield after the first cycle could be due to the loss of loosely bound enzyme from its support material.…”
Section: Reusability Of Immobilized Biocatalyst For Inulin Hydrolysismentioning
confidence: 99%